Problematika Pengembangan Kompetensi Digital Guru dalam Pendidikan Islam di Era Globalisasi - Tisnawati, Tin; Sukari, Sukari (Lembaga Yasin AlSys, 2024)
In the era of globalization, developing teachers' digital competence has become a significant challenge, particularly in the context of Islamic education, which must remain relevant to current advancements. This study aims to identify the problems and challenges in developing digital competence among teachers in Islamic educational settings in the globalization era. The research methodology used is library research, where primary and secondary data were collected from various books, journals, and literature related to digital competence and its relevance to Islamic education. The results show that while technology plays an essential role in enhancing the effectiveness of learning, many teachers in Islamic education still face challenges such as lack of training, limited access to technology, and resistance to change. This study recommends strengthening online-based training, improving technology infrastructure, and fostering collaboration with technology institutions to bridge the digital divide. This approach will help enhance teachers' professionalism and maintain the relevance of Islamic education in the digital era.